KEPATUHAN REMAJA DALAM MENERAPKAN PROTOKOL KESEHATAN UNTUK MENCEGAH COVID - Edy Soesanto; Nurul Ain; Dewi Setyawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Background: The Indonesian government has intervened to suppress the increasingly massive spread of the COVID-19 virus. one of them by implementation health protocols Wear masks, wash hands, keep your distance, and away from the crowds.. the level of adolescent compliance tends to be low in apply health protocol. Teenagers tend to ignore health protocols because they feel their bodies are healthy or immune. so they don't apply health protocols strictly. Research objective: Description of adolescent’s compliance in implementing health protocols as an effort to prevent Covid 19 at puskesmas air besar kota ambon. Research method This research used simple descriptive with a cross sectional approach, which the type of research that is carried out only once or immediately by looking for relationship of variables, where the data is collected at any time or the data is obtained at that time.The variable in this study is a single variable (univariate), that is adolescents in implementing health protocols as an effort to preventing Covid 19.The population in this study were 306 people. The sample in this study were 173 people. The cluster purposive sampling technique was used in determining the amound of respondents who would be the sample of the study, that is adolescents who were at puskesmas air besar kota ambon and were agree to be respondents. The research was implemented at puskesmas air besar kota ambon February to March 2021.Research Finding: The results of the univariate data analysis showed that 90 respondents were in the category of comforming to the health protocol covid 19.Conclusion: For the case of compliance, 90 respondents complied with the covid 19 health protocol.The results showed the importance of youth awareness in implementing health protocols as an effort to prevent the spread of covid 19